(untitled) (IITM Journal of Business Studies, 2024)
Past decade has seen a surge in shopping via online mode by Indian consumers. This is accompanied by a multifold increase in e-commerce platforms that are catering to the diverse needs of these customers. Yet some e-commerce platforms remains more popular in the market and others fade out fast. This study is an attempt to investigate the popular e-commerce platforms among Indians in categories namely, food, shopping, entertainment and transport (cab service). Further, the study also explores the influence of demographic variables (gender & age) on the online shopping behavior of Indian consumers. Online survey-based questionnaire was used to collect data from the respondents. Data analysis and hypotheses testing was performed using Chi-square test. Analysis revealed that age differences were important factor influencing the online shopping behavior of consumers in India in comparison to gender differences. The findings of the current study will help e-commerce platforms in strategizing themselves to lure the untapped age groups in India as more and more consumers are becoming comfortable with surfing, ordering and purchasing via the digital mode.